Removing Discrimination in Public Service: Braille E-Ticket Drug Health Services for People with Visual Disabilities - Putra, Fadillah (Indonesian Journal of Disability Studies, 2024)
The use of assistive technology in public sector services is an effort to reduce discrimination in public services. This study aims to analyse the continuity of the BREXIT (Braille E-Ticket Extraordinary Access for Visual Disabilities) innovation in improving the quality of health services for persons with visual disabilities in Malang City, Indonesia. The variables used consisted of the Service Innovation Variable (X) and the Public Service Quality Variable (Y). The data analysis technique used is the Multidimensional Scaling (MDS) method with the software Rapfish (Rapid Appraisal of Fisheries) 3.1 for Windows. The results showed that the BREXIT program succeeded in reducing the perception gap between people with disabilities (visually impaired) compared with non-disabilities, especially in health services at Janti Health Center Malang City, Indonesia.